2012
DOI: 10.5005/jp-journals-10015-1154
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrush Abrasion of Resin Composites with Different Filler Concepts

Abstract: Purpose: To investigate the effect of tooth brushing wear with and without calcium carbonate slurry on four commercial resin composites based on different filler concepts. Materials and methods:One nanofiller composite MI FIL (MFI, GC), one conventional hybrid type Venus (VEN) and two nanohybrid composites Venus Diamond (VED) and Venus Pearl (VEP) all from Heraeus Kulzer were examined. Forty beam-shaped specimens (12 × 3 × 3 mm) from each product were prepared and subdivided in two equal groups for pregrinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…and Bulk Fill Flowable Based composite (Dentsply). Although the mentioned later two types of composite fillers have same average cluster size, it is clear that the non-aggregated zirconia/silica cluster filler presented in Filtek Bulk Fill Posterior Restorative (3M, ESPE) can resist the toothbrushing abrasion more effectively than triethylene glycol dimethacrylate (TEGDMA) presented in Bulk Fill SDR (Dentsply) [32]. Notably, in the present study, the Tetric N-Ceram bulk fill (Ivoclar Vivadent) demonstrated more statistical significant differences in surface roughness compared to other two types of composites.…”
Section: Discussionmentioning
confidence: 99%
“…and Bulk Fill Flowable Based composite (Dentsply). Although the mentioned later two types of composite fillers have same average cluster size, it is clear that the non-aggregated zirconia/silica cluster filler presented in Filtek Bulk Fill Posterior Restorative (3M, ESPE) can resist the toothbrushing abrasion more effectively than triethylene glycol dimethacrylate (TEGDMA) presented in Bulk Fill SDR (Dentsply) [32]. Notably, in the present study, the Tetric N-Ceram bulk fill (Ivoclar Vivadent) demonstrated more statistical significant differences in surface roughness compared to other two types of composites.…”
Section: Discussionmentioning
confidence: 99%
“…Individual oral hygiene procedures by using tooth brush also play a significant role. Brushing time and the composite's microstructure and composition has an influence to the degree of roughness [9,10,22,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that toothbrushing without dentifrice had almost no effect on wear of hard tissues. [3][4][5][6] Commonly, it is believed that hard toothbrushes cause more wear on dental hard tissues and restorative materials than soft ones. However, unexpectedly several research reports confirmed, that hard toothbrushes in combination with abrasive toothpaste caused less abrasion than soft brushes with dentifrice.…”
Section: Introductionmentioning
confidence: 99%